Extraordinary women journalists - Price-Groff, Claire (New York : Children's Press, 1997)
Profiles the life and work of notable women journalists, including Sarah Hale, Margaret Fuller, and Nellie Bly.
Includes bibliographical references (p. 253-260) and index.
English language and literature.
Keywords: Women journalists -- Biography -- Juvenile literature; Journalists